SO survey of massive cores. Issue Volume 13:Issue S332(2017) (4th September 2018) - Zinchenko, Igor; Henkel, Christian
Abstract: We present the results of a survey of several tens of dense high mass star forming (HMSF) cores in three transitions of the SO molecule at 30 and 100 GHz with the 100-m Effelsberg and 20-m Onsala radio telescopes. The physical parameters of the cores are estimated from the line ratios and column densities. Relative abundances are derived as well.